دراسة أوجه القراء بين السورتين وآراء العلماء فيها - سندي، دعاء بنت زهير بن عبدالرحيم (جامعة الأزهر - كلية أصول الدين والدعوة بالمنوفية, 2018)
الحمد لله رب العالمين، والصلاة والسلام على نبينا محمد، وعلى آله وصحبه أجمعين، وبعد: فإن هذا البحث بعنوان: (دراسة أوجه القراءة بين السورتين وآراء العلماء فيها)، وقد قسمت خطة البحث إلى مقدمة وما يتبع لها، وتسعة مباحث تفصيلها كالآتي: المبحث الأول: مدخل في التعريف بمصطلح القراءة والرواية والطريق والوجه. المبحث الثاني: ماهية الأوجه العددية بين السورتين، ونشأتها. المبحث الثالث: مناهج المؤلفين في ذكر الأوجه العددية بين السورتين. المبحث الرابع: مظان الأوجه، والطريقة المتبعة في عرضها. المبحث الخامس: آراء العلماء في الأوجه العدد بين السورتين. المبحث السادس: العلوم التي يحتاج إلى معرفتها القارئ لاستخراج الأوجه بين السورتين. المبحث السابع: تحرير العوارض المجتمعة. المبحث الثامن: تطبيق على كيفية حساب الأوجه بين السورتين بطريقة التسوية وطريقة التفرقة بين العوارض بدون استخدام الضرب الحسابي من كتاب قرة العين للخليجي. المبحث التاسع: تطبيق على كيفية حساب الأوجه بين السورتين بطريقة التفرقة بين العوارض بالضرب الحسابي، وطريقة التفرقة بين العوارض بدون استخدام الضرب الحسابي من كتاب غيث النفع للسفاقسي. وقد ختمت البحث بخاتمة ذكرت فيها أبرز ما توصلت إليه من نتائج وتوصيات ومن أبرزها: أن طريقة استخدام الضرب الحسابي في حساب الأوجه التي انتهجها الجعبري والعراقي والنشار فيها خلط وتركيب للطرق والروايات وهو متفق على عدم جوازه، وأن أصح الطرق طريقة التسوية أو التفرقة بين العوارض المجتمعة بدون استعمال الضرب الحسابي. ثم أتبعت الخاتمة بفهرس المصادر، وفهرس الموضوعات، والله أعلم وأحكم، وصلى الله على نبينا محمد وعلى آله وصحبه أجمعين.
All praises be to Allah, prayers and peace be upon our Prophet Mohammad, his family and companions. The current thesis is titled “Study of the Reciters’ Views between the Two Surats and Scholars’ Views therein). The study has been divided into an introduction and nine parts with details as follows: Part one: an introduction to the definition of the reciters term, narration, way and method. Part two: Identification of numerical difference between the two surats and their beginning. Part three: methodology of writers in explaining the numerical difference between the two Surats. Part four: uncertain views of difference between the two Surats and methods followed for their explanation. Part five: scholars views in the numerical differences between the two Surats. Part six: Knowledge required for the reciter to recognize the difference between the two Surats. Part seven: Explanation of society issues. Part eight: Application on how to consider the numerical difference between the two Surats by equalization and difference between these differences without the mathematical multiplication from the Quratalain book of Alkhaleji. Part nine: Application on how to consider the numerical difference between the two Surats by distinction and difference between these differences and by using the mathematical multiplication; and by distinction and difference between these differences and without using the mathematical multiplication from Ghaith Alnafa book of Alsafaqsi. The researcher concluded her thesis with the following results and recommendation; among them: The mathematical multiplication method used in calculating adopted by Algabari, Aleraqi and Alnashar has a mixing and combination of methods and narrations which is agreed on not permitting. It is agreed that the best methods are equalizing or differing between the society differences without using mathematical multiplication. The conclusion is followed by the index of resources and topics of the thesis. All knowledge and wisdom be to Allah, and all prayers on our Prophet Mohammad, his family and companions.
Keywords: القرآن الكريم -- القراءات القرآنية -- القراء العشرة -- أحكام التلاوة